Green economy empowerment for MSMEs: AI-integrated organic waste processing technology from industry and agriculture to drive innovation in alternative poultry feed products - Wijaya, Dewa Kusuma; Santoso, Heru Agus; Setyaningrum, Ratih (Community Empowerment, 2025)
This community service activity aimed to empower Repro Micro, Small, and Medium Enterprises (MSMEs) in Semarang City to process organic waste, specifically, milk protein waste from the bread industry and banana tree waste from agriculture, into poultry feed pellet products. These products are intended to support livestock food security, environmental management, and social empowerment. The problem-solving method was implemented through an applied green economy approach, engineering a series of poultry feed pellet production machines integrated with an Artificial Intelligence (AI) system. The realization of this engineered technology series adheres to several technical standards and is designed with multi-feature mechanisms: coarse chopping, fine chopping, pulverizing, and pellet molding. The integration of the AI system serves as a virtual assistant to guide the partner in optimally composing the raw material mixture and simultaneously predict the resulting content based on quality parameters. This integration aims to enhance process effectiveness through improved quality outcomes while maintaining production efficiency. The results of the program realization show that the partner is able to utilize the technology effectively to independently produce poultry feed pellets at a cost of approximately IDR 5,850 per kg. Furthermore, the program's impact has demonstrated an ability to enhance self-reliance, competitiveness, environmental awareness, and business sustainability, thereby contributing to community welfare and advancing the people's economy at the MSME level.